2018
DOI: 10.15419/bmrat.v5i5.443
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fetal middle cerebral artery versus umbilical artery color Doppler ultrasound for predicting neonatal outcome in complicated pregnancies with fetal growth restriction

Abstract: Background: Although using Doppler ultrasonography of umbilical structures is a common method for predicting prenatal adverse outcome, recent studies have proposed the importance of middle cerebral artery (MCA) Doppler assessment for antenatal monitoring. The aim of the present study was to compare alterations in the fetalMCAversus umbilical artery (UA) pulsatility indices (PI) in complicated pregnancies by fetal growth restriction (FGR). Methods: A cohort study was carried out in Yas Hospital (Tehran, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…In our study, out of 100 patients, (38%) had first gravidity, (29%) had gravida 2, (27%) had 3 rd gravidity and only (6%) patients had 4 th gravidity. In consonance to our study Anjum S et al, (2019) also reported maximum percentage of primigravidae [10] . Another study by Geeta M et al, (2016) showed 40% primigravidae patients [12] .…”
Section: Results and Observationssupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, out of 100 patients, (38%) had first gravidity, (29%) had gravida 2, (27%) had 3 rd gravidity and only (6%) patients had 4 th gravidity. In consonance to our study Anjum S et al, (2019) also reported maximum percentage of primigravidae [10] . Another study by Geeta M et al, (2016) showed 40% primigravidae patients [12] .…”
Section: Results and Observationssupporting
confidence: 93%
“…However, we found that (52%) did not have any associated risk factor. In similar kind of study by Anjum S et al, (2019), pregnancy induced hypertension was present in (38%) patients making it most important risk factor, diabetes in 2% cases, anaemia in (30%) cases [10] . So, this study was similar to our study in proving pregnancy induced hypertension as most important risk factor.…”
Section: Results and Observationsmentioning
confidence: 59%
See 1 more Smart Citation
“…Study further disclosed that mean middle cerebral PI in IUGR group was 1.15±0.26 and among normal females was 1.63±0.36. The findings were determined to be significant statistically (P 0.001).Virtually the results of our study are comparable with a study undertaken by Sharbaf 31 and partners in 2018 who asserted that mean middle cerebral PI in IUGR group was 1.405±0.377 and among normal females was 1.799±0.412 while the results were found statistically significant (P <0.000).…”
Section: Discussionsupporting
confidence: 87%
“…4 Fetal and maternal doppler ultrasound helps in detection of compromised IUGR fetus by doing timely intervention which is main objective of antenatal care. 5 IUGR are mainly due to increased resistance within the placental circulation which leads to decrease in velocity in the feeding arteries especially during diastole than systole. Disproportionate slowing of diastolic relative to systolic flow leads to elevation of a number of Doppler indices, including the systolic/diastolic ratio and the pulsatility index.…”
Section: Introductionmentioning
confidence: 99%